Control of inhibition by the direct action of cannabinoids on GABAA receptors - Golovko, Tatiana; Min, Rogier; Lozovaya, Natalia; Falconer, Caroline; Yatsenko, Natalia; Tsintsadze, Timur; Tsintsadze, Vera; Ledent, Catherine; Harvey, Robert J.; Belelli, Delia; Lambert, Jeremy J.; Rozov, Andrei; et al. (Cerebral cortex, 2015)
Cannabinoids are known to regulate inhibitory synaptic transmission via activation of presynaptic G protein-coupled cannabinoid CB1 receptors (CB1Rs). Additionally, recent studies suggest that cannabinoids can also directly interact with recombinant GABAA receptors (GABAARs), potentiating currents activated by micromolar concentrations of γ-aminobutyric acid (GABA). However, the impact of this direct interaction on GABAergic inhibition in central nervous system is unknown. Here we report that currents mediated by recombinant GABAARs activated by high (synaptic) concentrations of GABA as well as GABAergic inhibitory postsynaptic currents (IPSCs) at neocortical fast spiking (FS) interneuron to pyramidal neuron synapses are suppressed by exogenous and endogenous cannabinoids in a CB1R-independent manner. This IPSC suppression may account for disruption of inhibitory control of pyramidal neurons by FS interneurons. At FS interneuron to pyramidal neuron synapses, endocannabinoids induce synaptic low-pass filtering of GABAAR-mediated currents evoked by high-frequency stimulation. The CB1R-independent suppression of inhibition is synapse specific. It does not occur in CB1R containing hippocampal cholecystokinin-positive interneuron to pyramidal neuron synapses. Furthermore, in contrast to synaptic receptors, the activity of extrasynaptic GABAARs in neocortical pyramidal neurons is enhanced by cannabinoids in a CB1R-independent manner. Thus, cannabinoids directly interact differentially with synaptic and extrasynaptic GABAARs, providing a potent novel context-dependent mechanism for regulation of inhibition.